Increased Neutrophil to Lymphocyte Ratio in Patients With Resistant Hypertension - Belen, Erdal (J Clin Hypertens (Greenwich), 2015)
Resistant hypertension (RHT) is an important disease that causes an increase in cardiovascular risk, yet its etiology remains unclear. The authors aimed to investigate neutrophil/lymphocyte ratio (NLR) as an inflammation marker in patients with RHT. A total of 150 patients were included in the study and grouped according to their office and ambulatory blood pressure measurements. They were classified as having normotension (NT), controlled hypertension (CHT), or RHT. The RHT group had a significantly higher NLR than the CHT group (P=.03), and NLRs of both hypertension groups were significantly higher than those in the NT group (P<.001, for both). NLR and neutrophil count were found to be independent correlates for RHT in multivariate analysis (P<.001). NLR and neutrophil count are increased in RHT patients than both CHT and NT patients. This finding, which is defined for the first time in patients with RHT, may imply the importance of inflammation in blood pressure control.